2014
DOI: 10.2989/10220119.2013.858772
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a hand-held instrument for measuring condensed tannin concentration based on UV- and red-excited fluorescence

Abstract: Condensed tannins are ecologically important compounds in plants for several reasons, e.g. as herbivore deterrents or protecting photosynthetic tissues against ultraviolet radiation. The hand-held Dualex Series 4 instrument was originally developed for indirect determination of flavonol concentrations in crops. Flavonols are low-molecular-weight phenolics from which condensed tannins are synthesised. Therefore, it was expected that the Dualex's 'flavonol index' (range 0.00-3.00) could be used to predict conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Our results corroborated the findings of other studies of savanna woody plant responses to browsing that have shown that compensatory or over‐compensatory shoot production is a common response to various intensities of browsing (Scogings & Gowda 2020). However, because reduced stem diameter can be indicative of C exhaustion (Hester et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results corroborated the findings of other studies of savanna woody plant responses to browsing that have shown that compensatory or over‐compensatory shoot production is a common response to various intensities of browsing (Scogings & Gowda 2020). However, because reduced stem diameter can be indicative of C exhaustion (Hester et al .…”
Section: Discussionsupporting
confidence: 91%
“…The instrument has been successfully used to determine chemical responses of woody plants to browsing (Pellisier 2013). It has been successfully calibrated for indirectly measuring condensed tannin concentrations (acid-butanol assay, Sorghum tannin standard) in some savanna woody species including S. birrea (Scogings et al 2014) and has been successfully used to determine S. birrea chemical responses to nutrient fertilisation (Scogings 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The roots, leaves, and other parts of E. divinorum showed high tannin contents (36,37), which constitutes an inherent defense mechanism against herbivory of species in the Euclea genus (10). They are therefore widely used in Tanzania, Zimbabwe, Kenya, Botswana, and Yemen as purple ink, black dye for mats, wool, for tanning leather, basket ware, and other textiles, especially when a mordant of iron-rich mud is used after dyeing (11,(38)(39)(40)(41)(42).…”
Section: Non-medicinal (Textile Cosmeceutical and Economic) Uses Of E...mentioning
confidence: 99%
“…These measures are non-destructive and much more rapid than quantifying the within-leaf concentrations, but nevertheless strongly correlated to within-leaf concentrations (Goulas et al 2004). Moreover, anthocyanins and flavonols reflect well overall polyphenol concentrations under comparable conditions (Scogings 2014). We measured three leaves per tree, between leaf veins on both leaf faces.…”
Section: Measurements Of Leaf Traitsmentioning
confidence: 99%